Analysis of Clean Water Demand in Watudiran Village, Sikka Regency - Gode, Dicky; Nugroho, Laksono Djoko; Wulandari , Esti (Publica Scientific Solution, 2025)
Watudiran Village in Sikka Regency is a semi-arid area experiencing limited access to clean water due to the absence of an adequate piped water network. To develop an effective and sustainable clean water pipeline project, various baseline data are needed to support technical planning and guide appropriate investment decisions. This study aims to analyze clean water demand based on projected population growth and domestic water consumption standards. The method involves population projection using a geometric growth model and water demand estimation based on government standards, assuming a daily per capita consumption of 60 liters per person. The analysis covers the period from 2024 to 2039. The results show that the population of Watudiran Village is projected to increase from 1,871 people in 2024 to 2,559 people in 2039. Based on this assumption, the average daily water demand will reach 153,522 liters by the end of the projection period. The peak flow is estimated at 3.56 liters per second, using a peak factor of 2.0. These findings provide a quantitative foundation for designing the village’s clean water distribution system and serve as a key reference for rural infrastructure development planning.